2015
DOI: 10.1310/hpj5002-108
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Subcutaneous Ketorolac for Pain Management

Abstract: This Hospital Pharmacy feature is extracted from Off-Label Drug Facts, a publication available from Wolters Kluwer Health. Off-Label Drug Facts is a practitioner-oriented resource for information about specific drug uses that are unapproved by the US Food and Drug Administration. This new guide to the literature enables the health care professional or clinician to quickly identify published studies on off-label uses and determine if a specific use is rational in a patient care scenario. References direct the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 15 publications
1
12
0
2
Order By: Relevance
“…Short‐term use of ketorolac lacks the respiratory depressant effects of opiate analgesics but shares the toxic potentials of other nonsteroidal anti‐inflammatories . The major AEs related to ketorolac tromethamine treatments involve gastrointestinal bleeding, peptic ulcers, and perforation of the stomach, as well as prolonged platelet aggregation and a decline in renal functions . In the study reported here, a total dose of 120 mg ketorolac tromethamine administered via continuous subcutaneous infusion appeared to be safe and well tolerated in this study.…”
Section: Discussionmentioning
confidence: 62%
See 4 more Smart Citations
“…Short‐term use of ketorolac lacks the respiratory depressant effects of opiate analgesics but shares the toxic potentials of other nonsteroidal anti‐inflammatories . The major AEs related to ketorolac tromethamine treatments involve gastrointestinal bleeding, peptic ulcers, and perforation of the stomach, as well as prolonged platelet aggregation and a decline in renal functions . In the study reported here, a total dose of 120 mg ketorolac tromethamine administered via continuous subcutaneous infusion appeared to be safe and well tolerated in this study.…”
Section: Discussionmentioning
confidence: 62%
“…The treatments were separated by a washout period of ≥4 days. The total daily dose of 120 mg ketorolac tromethamine administered as 4 × 30 mg/mL intramuscular bolus injections is the standard course of treatment, and in several studies the same dose has been reported to be well tolerated when administered in a continuous subcutaneous infusion regimen to patients, and as such was chosen for this study …”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations